Cleaning Up Flaws in TLS Implementations. - Rescorla, Eric (Communications of the ACM, 2017)
The article discusses problems with TLS protocols in relation to complexity that compromises software security. Topics include the use of state machines from the organization OpenSSL, the lack of web browser support for the protocol SSLv3, and the strengthening of TLS in relation to the browser Firefox.